2008
DOI: 10.1089/dia.2007.0288
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward an In Vivo Surface-Enhanced Raman Spectroscopy Glucose Sensor

Abstract: We show successful use of the SERS glucose sensor in rats, making it the first in vivo SERS sensor. Furthermore, we demonstrate free space transdermal detection of a SERS signal through the rat's skin as an initial step toward developing a transcutaneous sensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 59 publications
3
90
1
2
Order By: Relevance
“…The phenomenon of surface-enhanced Raman scattering (SERS) [1][2][3][4] possesses a great potential in sensing and recognition [5][6][7] of molecular structures up to a single-molecule level. 8,9 In the SERS setup plasmon excitations supported by the noble metal substrate focus the probing laser field below the diffraction limit and also enhance the spontaneous emission from the analyte ABSTRACT The surface-enhanced Raman scattering (SERS) signal from an AgFON plasmonic substrate, recoated with benzenethiol, was observed to increase by about 100% upon heating for 3.5 min at 100º C and 1.5 min at 125º C. The signal intensity was found to increase further by about 80% upon a 10-s exposure to a high-intensity (3.2 kW/cm 2 ) 785-nm cw laser, corresponding to 40 mW in a 40±5-μm diameter spot.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of surface-enhanced Raman scattering (SERS) [1][2][3][4] possesses a great potential in sensing and recognition [5][6][7] of molecular structures up to a single-molecule level. 8,9 In the SERS setup plasmon excitations supported by the noble metal substrate focus the probing laser field below the diffraction limit and also enhance the spontaneous emission from the analyte ABSTRACT The surface-enhanced Raman scattering (SERS) signal from an AgFON plasmonic substrate, recoated with benzenethiol, was observed to increase by about 100% upon heating for 3.5 min at 100º C and 1.5 min at 125º C. The signal intensity was found to increase further by about 80% upon a 10-s exposure to a high-intensity (3.2 kW/cm 2 ) 785-nm cw laser, corresponding to 40 mW in a 40±5-μm diameter spot.…”
Section: Introductionmentioning
confidence: 99%
“…159 The next step involved implanting their substrate inside a living animal and verifying if the platform could provide quantitative accuracy in vivo. 160 Using Sprague-Dawley rats and SESORS, they demonstrated that consistent, stable, and accurate Raman measurements of glucose could be performed when the probe was implanted and surrounded by interstitial fluid (rather than blood). The SESORS approach eliminated the need to remove the platform from the rat and allowed direct detection of glucose with high accuracy.…”
mentioning
confidence: 99%
“…This specific site had a low surface coverage (approximately three per colloidal particle); however, the authors claimed an enhancement of 10 6 . This enhancement was believed to be due to a charge transfer mechanism.…”
Section: Resultsmentioning
confidence: 97%
“…Detection and discrimination of specimens in complex biological media are also a necessity, together with reproducible results, cost and time effectiveness, and ease of use under most conditions. Due to its unique ability to provide ultrasensitive detection limits, SERS has been used to detect molecular modifications involved in disease, such as cancer, 3,5 diabetes, 6 etc.…”
Section: Introductionmentioning
confidence: 99%